Sentence-Completion Method in Eleven and Twelve Year Old Pupil Assessment - Dereškevičius, Pranas (Acta Paedagogica Vilnensia, 1997)
The paper presents development of the sentence-completion method, evaluating the present status technology and reviewing the structure and four major elements of sentence- completion tests. The Hart Sentence-Completion Test for Children was selected to illustrate the present state of technology by tracking its theoretical conceptualization through its stages of development. In our version the method was used for psycho-educational assessment with reference to 11 and 12 year old children. There are many versions of children's sentence-completion tasks. The version used in our practice is discussed. Our sentence-completion test was developed to elicit responses in twelve different dimensions: family, peers, school, classmates, teachers, lessons, learning, need orientations, past, future, self-regard, and affects. Although these are not typically standardized, they provide one means of gathering important information from children. The method was used for the eleven and twelve year old pupil assessment. The second half of the paper is devoted to the presentation of the empirical evaluation of pupils' answers, sentence-completion responses - which an individual completed in writing - and their acceptance of their peers, school, and teachers. The children's sentence-completion responses reflected changing attitudes towards the opposite sex. We compared the perceptions of the opposite sex expressed by boys and girls with this technique and compared their response contents. In conclusion, the importance of the thesis on the sentence-completion method's major limitations in the evaluation of eleven and twelve year old children's responses of the sentence-completion difficulties of interpretation are emphasized.